Three new national records from Kon Chu Rang Nature Reserve, Vietnam: Euphorbia bokorensis, Glochidion geoffrayi and Lysimachia nutantiflora - Nuraliev, Maxim S.; Toyama, Hironori; Hu, Chi-Ming; Luo, Shi-Xiao; Lyskov, Dmitry F.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Quang, Bui Hong; Binh, Tran Duc; Hoan, Duong Thi (Phytotaxa, 2022)
We report three species of angiosperms found in Kon Chu Rang Nature Reserve representing new records for Vietnam. Kon Chu Rang Nature Reserve is located in the Central Highlands of Vietnam, being a part of a recently established Kon Ha Nung Highland Biosphere Reserve. Euphorbia bokorensis (Euphorbiaceae) appears to be widely distributed throughout the Central Highlands of Vietnam, although it was earlier known from Cambodia and Laos only. Pistillate flowers are for the first time described for E. bokorensis. Glochidion geoffrayi (Phyllanthaceae) was considered endemic to southern Cambodia, and Lysimachia nutantiflora (Primulaceae) was only known from Guangxi, China. For each species, we provide analytical photographs, information on its habitat, phenology, distribution and studied specimens.